Exploring the Potential of Architectural Semiotic in Realizing the Smart City Concept - Muktiono, Ayub (International Publisher (YAPENBI), 2024)
Smart City is an urban development paradigm that integrates information and communication technology to improve the quality of life of residents, efficient resource management and environmental sustainability. Architectural semiotic, as the embodiment of visual language in architecture, has an important role in creating a smart and sustainable environment. This research aims to explore the potential of architectural semiotic in realizing the Smart City concept. This research uses a qualitative approach with descriptive methods. The results of this research reveal that the potential of architectural semiotic in the Smart City concept can be optimized through steps such as literature study and concept analysis, use of modern technology, interdisciplinary collaboration, community participation, and development of design guidelines. By engaging architects, data scientists, engineers, and the public, and creating practical guidance, this research details how architectural semiotic can be effectively integrated in smart city development. It is hoped that these results will make a significant contribution in creating a smart, efficient, aesthetic and sustainable urban environment in accordance with Smart City principles.